The Effect of the Oral Administration of Leucine on Endothelial Function, Glucose and Insulin Concentrations in Healthy Subjects - Argyrakopoulou, Georgia; Kontrafouri, Paraskevi; Eleftheriadou, Ioanna; Kokkinos, Alexander; Arapostathi, Christina; Kyriaki, Despoina; Perrea, Despoina; Revenas, Constantinos; Katsilambros, Nicholas; Tentolouris, Nicholas (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective The aim of our study was to investigate the potential differential effect of hyperglycaemia and hyperinsulinaemia induced by glucose infusion alone and in combination with leucine consumption on endothelial function in healthy individuals.Methods Ten male volunteers were examined in random order twice. In one visit, they consumed 250 ml water (baseline) and 30 min later glucose was infused iv. In the other visit, they consumed 250 ml water with 25 g of leucine and 30 min later the same amount of glucose was infused. Serum glucose and insulin were measured at baseline and every 10 min after glucose infusion for 1 h. Endothelial function was evaluated by measurement of flow mediated vasodilatation (FMD) at baseline, 10 and 60 min after glucose infusion.Results In both visits, glucose levels increased to the same degree, whereas insulin response was significantly higher after leucine administration. FMD values declined significantly compared to baseline 10 min after glucose infusion in the control visit (6.9±2.7 vs. 3.2±3.5%, respectively, p=0.006), while no significant change was observed when glucose infusion was followed by leucine consumption.Conclusions Acute hyperglycaemia impairs endothelial function in healthy male individuals. Leucine administration prevents hyperglycaemia-mediated endothelial dysfunction probably due to enhanced insulin secretion.
Keywords: Hyperinsulinaemia; hyperglycaemia; endothelial dysfunction; flow-mediated dilatation